Convective boundary layer flow and heat transfer of williamson hybrid ferrofluid with various effects - Wan Muhammad Hilmi, Wan Rosli (2024)
The flow and convective heat transfer of ferrofluid plays an important role in engineering, electronics, and medicine. Such flows are widely applied in hi-fi speakers, computer hard disks, cancer treatment, magnetic resonance imaging, and other diagnostic tests. Ferrofluid usually contains ferroparticles made from oxide, which has low thermal conductivity, thus providing limited heat transfer performance. Combining the ferroparticles with other highly thermally conductive nanoparticles in the based fluid, known as hybrid ferrofluid, is expected to enhance heat transfer over the ferrofluid. Generally, the based fluids employed in engineering and industrial applications such as polymer solutions, blood, and paint are non-Newtonian fluids with pseudo-plastic characteristics. Due to the lack of experimental data and theoretical analysis available to verify such an explanation for a pseudo-plastic hybrid ferrofluid flow, a study on this topic is needed in order to improve and explore its capabilities in flow and convective heat transfer. In this study, the pseudo-plastic fluid flow is modeled based on the Williamson model. Three problems are considered in this research, which are the stagnation point flow over a stretching sheet, the flow over a permeable stretching sheet with the presence of thermal radiation, and the flow over a moving plate with viscous dissipation effects in Williamson hybrid ferrofluid. The governing equations for each problem are modeled in the form of non-linear partial differential equations. These equations are then transformed into ordinary differential equations using the similarity transformation and solved numerically using the Keller-box method (KBM). MATLAB software is used to compute the numerical codes for all the problems. The magnetic parameter, stretching parameter, Williamson fluid parameter, permeability rate parameter, thermal radiation parameter, moving plate parameter, and viscous dissipation parameter are the parameters considered in this research. Comparisons with other types of hybrids ferrofluid and different ferroparticle volume fractions are also considered. The results show that Williamson hybrid ferrofluid potentially provides better performance in heat transfer capability compared to ferrofluid with the same volume of nanoparticle volume fraction. Nusselt number increases as the magnetic parameter, stretching parameter, permeability rate parameter, moving plate parameter, and thermal radiation parameter are induced, thus reducing the thermal boundary layer thickness. The increased magnetic parameter increases the skin friction coefficient for all problem studies. Skin friction coefficient values decrease as stretching and moving parameters increase, which increases momentum in the boundary layer flow. As Williamson parameter increases, the skin friction coefficient increases while Nusselt number does not affected, as shown in Nusselt number formula.